2003
DOI: 10.1210/en.2002-220292
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α Gene Deficiency Enhances Androgen Biosynthesis in the Mouse Leydig Cell

Abstract: Leydig cells, which produce the primary male steroid hormone testosterone (T), express the two estrogen receptor (ER) subtypes, ERalpha and ERbeta, and have the capacity to convert testosterone to the natural estrogen 17beta-estradiol. Thus, Leydig cells are subject to estrogen action. The development of transgenic mice that are homozygous for targeted deletion of genes encoding the ER subtypes provides an opportunity to examine the role of estrogen in Leydig cell function. In this study androgen biosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
88
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 55 publications
14
88
0
Order By: Relevance
“…This elevation of testosterone appears to be independent of LH stimulation (Eddy et al, 1996;McDevitt et al, 2007;Wersinger et al, 1999) and more likely reflects increased androgen biosynthesis of individual Leydig cells (Akingbemi et al, 2003). We have demonstrated that serum T levels are completely restored in the ERα −/AA male (Fig.…”
Section: Testicular Function and Testosterone Production In The Malementioning
confidence: 54%
See 1 more Smart Citation
“…This elevation of testosterone appears to be independent of LH stimulation (Eddy et al, 1996;McDevitt et al, 2007;Wersinger et al, 1999) and more likely reflects increased androgen biosynthesis of individual Leydig cells (Akingbemi et al, 2003). We have demonstrated that serum T levels are completely restored in the ERα −/AA male (Fig.…”
Section: Testicular Function and Testosterone Production In The Malementioning
confidence: 54%
“…In addition to the abnormal morphological features of the testis, serum testosterone levels are significantly elevated in ERαKO males (Akingbemi et al, 2003;Delbes et al, 2005;Eddy et al, 1996;McDevitt et al, 2007;Wersinger et al, 1999). This elevation of testosterone appears to be independent of LH stimulation (Eddy et al, 1996;McDevitt et al, 2007;Wersinger et al, 1999) and more likely reflects increased androgen biosynthesis of individual Leydig cells (Akingbemi et al, 2003).…”
Section: Testicular Function and Testosterone Production In The Malementioning
confidence: 97%
“…Oestrogen signalling is involved in many processes in male reproduction, and is essential to achieve normal fertility, as indicated in mammals in studies conducted with oestrogen receptor (ER) knockout mice (Eddy et al 1996, Hess et al 2000, Akingbemi et al 2003, Gould et al 2007. Furthermore, oestrogenic feedback on the hypothalamus and pituitary controls the synthesis and release of gonadotropins in mammals, and hence the testicular synthesis of androgens ( Jong et al 1975, Lindzey et al 1998, Turner et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility cannot be completely ruled out because we did not measure circulating levels of gonadal steroids at the time of behavioral tests in the present study. However, this possibility seems less likely because previous studies have reported that adult αERKO male mice have rather elevated levels of testosterone (28,29). Nevertheless, it is necessary to investigate whether similar behavioral effects of prepubertal ERα knockdown may be observed in mice gonadectomized and treated with a fixed amount of testosterone before behavioral testing in adulthood.…”
Section: Discussionmentioning
confidence: 99%